Analyzing Teacher Performance in the Digital Era: The Interplay of Cyberloafing Behavior, Digital Competence, and Work Motivation (Case Study: 3 Muhammadiyah Vocational Schools in Cianjur) - Heri Herawan; Nuraeni Nuraeni (Dinasti International Journal of Education Management And Social Science, 2025)
This study explores the influence of cyberloafing behavior, digital competence, and work motivation on teacher performance at SMK Muhammadiyah Cianjur. Using a quantitative approach, this study involved 100 teachers as samples and analyzed the data using the Partial Least Squares (PLS) method. The results showed that digital competency has a significant positive effect on work motivation and teacher performance, while cyberloafing has a negative impact on performance. Work motivation was found to mediate the relationship between digital competencies and teacher performance. This research highlights the importance of digital competency training to support technology-based learning, while reducing cyberloafing behavior that can reduce productivity. Institutional support and clear policies are important factors in motivating teachers to achieve optimal performance. The findings offer practical and theoretical insights to improve education quality through more effective human resource management in the digital era.